ACADEMIC SUPERVISION WITH COACHING TECHNIQUES TO IMPROVE TEACHER PERFORMANCE (MULTI-SITE STUDY AT RANGGEH AND GAYAM ELEMENTARY SCHOOL, GONDANGWETAN DISTRICT, PASURUAN REGENCY) - Ismawati; Taufiq Harris; Suyitno (Yayasan Amanah Nur Aman, 2026)
This research is motivated by the real challenges faced by primary school teachers, such as low teaching motivation, the use of monotonous learning methods, and limited mastery of information technology. Furthermore, the implementation of conventional academic supervision often fails to provide a significant impact due to a lack of effective follow-up in encouraging independent professional development. This study aims to describe and analyze the implementation stages of coaching techniques in academic supervision, identify implementation challenges, and evaluate its impact on teacher performance at SDN Ranggeh and SDN Gayam, Gondangwetan District, Pasuruan Regency. The research method employed is a qualitative approach with a multi-site study design. Primary data were collected through in-depth interviews with key informants consisting of principals, school supervisors, as well as senior and junior teachers. Additionally, secondary data were obtained through observation and documentation related to the planning and results of academic supervision. Data analysis was conducted systematically through the processes of data reduction, data display, and conclusion drawing to ensure the validity of the findings. The expected result of this research is the realization of a collaborative coaching-based academic supervision model using the TIRTA (Goal, Identification, Action Plan, Responsibility) and GROW (Goal, Reality, Options, Will) models. The implementation of this approach is expected to enhance teachers' pedagogical and professional competencies, foster internal motivation, and encourage learning innovations that directly impact the improvement of educational quality and student character in schools.